The SmartAG Partner: CCAFS East Africa Quarterly Newsletter, October - December 2014 - CGIAR Research Program on Climate Change, Agriculture and Food Security (CGIAR Research Program on Climate Change, Agriculture and Food Security, 2014)
We are pleased to announce the launch of a web based knowledge platform, the Climate and Agriculture Network for Africa (CANA). This new regional platform seeks to enhance science – policy dialogue on climate-smart agriculture in Africa in order to enhance food security and livelihood improvement for African farmers. In this issue of the SmartAG Partner, CCAFS East Africa quarterly newsletter, read more about how CCAFS and partners helped farmers contribute to the UNFCCC deliberations at a side event held in Lima during the 20th session of the Conference of the Parties to the UNFCCC (COP 20). Participants at the side event organized by CCAFS and Kenya’s Ministry of Environment Water and Natural Resources (MEWNR) recommended that a collaborative approach to research would ensure the uptake of agricultural technologies. Under science news, find out how we need to re-adapt agriculture to overcome climate change related stresses. We also present how a project on soil analysis in Lushoto, Tanzania is helping scientists map out the true soil complexities within the landscape putting them in a good position to give advice on appropriate farming practices. Read more about the changing agricultural practices in climate-smart villages across East Africa that are being driven by CGIAR knowledge. Under field updates, two champion farmers, through climate-smart innovations have been able to combat climate variability. They are reaping huge harvests and sharing lessons within their communities. There are also highlights of the climate adaptation journey taken by 16 farmers from the Nyando climate-smart villages. Finally, see how a TV program is changing farming practices by making climate information easily accessible to farmers across East Africa.